Microstructure Formation and Dry Reciprocating Sliding Wear Response of High-Entropy Hypereutectic White Cast Irons - Willian Martins Pasini; Wojciech Polkowski; Tomasz Dudziak; Carlos Alexandre dos Santos; Vinicius Karlinski de Barcellos (Metals)
White cast irons (WCI) are widely used in industries requiring high wear resistance due to their microstructure consisting of hard carbides dispersed within a metallic matrix. This study focuses on developing wear-resistant multi-component hypereutectic high chromium cast irons, merging concepts of high entropy alloys with the conventional metallurgy of white cast irons, specifically exploring the influence of carbide-forming elements such as V, Mo, and Ni on solidification behavior, microstructure, and wear performance. The research investigates the solidification process of the alloys using Computer-Aided Cooling Curve Analysis (CA-CCA) and characterizes the microstructures through X-ray diffraction (XRD) and scanning electron microscopy (SEM). The wear behavior of the developed alloys is evaluated through reciprocating sliding wear tests, revealing the impact of varying chemical compositions on wear resistance. The results demonstrate that high-entropy white cast iron (HEWCI), particularly those enriched with carbide-forming elements, exhibit superior abrasion resistance compared to conventional high-chromium cast irons. The alloy with 2 Mo and 4 V content showed the best performance, presenting the lowest wear rate (61.5% lower than HCCI alloy) and CoF (values ranging from 0.20 to 0.22) due to the highest concentration of V carbides.